Donor pigs for clinical islet xenotransplantation: Review and future directions - Shinichi Matsumoto; Sadaki Asari; Yoshihide Nanno; Hiroyuki Nakamura; Taisuke Okawa; Takumi Fukumoto (Cell Transplantation)
Allogeneic islet transplantation becomes a viable option for patients with unstable type 1 diabetes. However, considering the huge number of patients with type 1 diabetes, human donor shortage is a serious issue. To overcome the donor shortage issue, xenotransplantation is an attractive option. In fact, clinical islet xenotransplantation has been conducted since 1990s. The first clinical trial was performed using fetal pigs and demonstrated the porcine pancreatic tissue could survive in human body with immunosuppressive strategies. To scale up the islet production, Canadian group established a method for islet isolation from neonatal pigs. Their method has been used for clinical islet xenotransplantation in New Zealand, Russian, Mexico, Argentina, and China. Recently Korean group published a clinical protocol for islet xenotransplantation using adult pigs. For the next generation of islet xenotransplantation, gene-modified pigs were created. Especially “superislets” created by Belgian group demonstrated promising preclinical outcomes. With advanced donor pigs, islet xenotransplantation might become a suitable treatment for the majority of type 1 diabetic patients.